Intrathymic maturation of murine T lymphocytes from CD8+ precursors. - Guidos, C J (1989)
The CD4-8- thymocyte subset contains immature precursors for phenotypically and functionally mature CD4+8- and CD4-8+ thymocytes and peripheral T cells, as well as nonmature CD4+8+ thymocytes, most of which die in situ. The intrathymic death of most thymocytes is probably related to selective influences that ensure that only those precursors bearing self-major histocompatibility complex (MHC)-restricted and self-tolerant T-cell antigen receptors (TCR) survive to complete the maturation process. Interactions between surface molecules on thymocytes (TCR, CD4, and CD8) and thymic stromal cells (MHC proteins) are critical to repertoire selection. To understand this process, the lineage relationships among immature, nonmature, and mature thymocytes must be defined. We have examined directly the precursor-progeny relationships among CD4+8-, CD4-8+, and CD4+8+ murine thymocyte subsets by assessing their short-term (less than 5 days) developmental potentials following intrathymic injection into Thy-1 congenic, unirradiated host mice. Our results identify TCR-/lo CD4-8+ and TCRlo CD4+8+ blast cells as sequential intermediates in the development of mature TCRhi CD4+8- and TCRhi CD4-8+ thymocytes from CD4-8- precursors, thus defining at least one intrathymic maturation pathway for T lymphocytes.